A Computational Tool for Erosion/Corrosion Prediction in Oil/Gas Production Facilities - Mohyaldinn, Mysara Eissa (2010)
Sand production with oil and gas give rise to internal wear of pipelines and pipe components due to continuous impact of sand particles on the target material. This phenomenon is referred to as “sand erosion” and is highly expected to take place in pipe components where flow diverts or accelerates. The presence of corrosive components, on the other hand, causes degradation of the pipe material due to chemical and electrochemical interactions between the corrosive fluids and the target materials. This phenomenon is referred to as “corrosion” and it is expected to take place in all conduits containing corrosive fluids. The presence of both erodent and corrosive components in a process causes the socalled “erosion-corrosion”, which generates wear magnitude greater than the sum of wears caused by individual erosion and corrosion mechanisms. A computational code to predict erosion, corrosion, and erosion-corrosion in pipes and components has been developed to serve as an accessible, accurate, and cheap erosion/corrosion predictive tool.